(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This research examines the regional effects of climate change in South Asia, Sub-Saharan Africa, and Latin America from 1991 to 2020, concentrating on temperature, precipitation, and socio-economic vulnerability. The study utilizes secondary datasets from ERA5, CRU, EM-DAT, FAO, World Bank, and ND-GAIN to implement the IPCC Risk Framework (Risk = Hazard × Exposure × Vulnerability) for the comparison of climate hazards across areas. The results show that South Asia saw the biggest rise in temperature (+1.1°C) and a 6% drop in precipitation. This caused more hot days and changes in the monsoon. Sub-Saharan Africa had the highest overall climate risk because of less rain (–10%), more droughts, and a low ability to adjust because of economic and infrastructure problems. Latin America experienced modest climate stress but gained advantages from comparatively greater adaptation capacity and institutional resilience. The comparative study highlights the imperative for region-specific adaptation solutions, including climate-smart agriculture, early warning systems, social support, and green infrastructure, to enhance long-term resilience.